2016
DOI: 10.1111/nep.12798
|View full text |Cite|
|
Sign up to set email alerts
|

An expanded nationwide view of chronic kidney disease in Aboriginal Australians

Abstract: We summarize new knowledge that has accrued in recent years on chronic kidney disease (CKD) in Indigenous Australians. CKD refers to all stages of preterminal kidney disease, including end‐stage kidney failure (ESKF), whether or not a person receives renal replacement therapy (RRT). Recently recorded rates of ESKF, RRT, non‐dialysis CKD hospitalizations and CKD attributed deaths were, respectively, more than sixfold, eightfold, eightfold and threefold those of non‐Indigenous Australians, with age adjustment, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 31 publications
2
42
0
Order By: Relevance
“…Australia's Indigenous population experiences a disproportionally high burden of chronic disease compared to non‐indigenous Australians, including kidney disease, with rates of RRT eightfold higher in the Indigenous population . Reduced access to transplant waitlisting and transplantation for Indigenous people has previously been reported and post‐transplant outcomes are poorer for Indigenous recipients .…”
Section: Discussionmentioning
confidence: 99%
“…Australia's Indigenous population experiences a disproportionally high burden of chronic disease compared to non‐indigenous Australians, including kidney disease, with rates of RRT eightfold higher in the Indigenous population . Reduced access to transplant waitlisting and transplantation for Indigenous people has previously been reported and post‐transplant outcomes are poorer for Indigenous recipients .…”
Section: Discussionmentioning
confidence: 99%
“…While Indigenous status is an important determinant of CKD in the Australian population, gender is an important determinant of the need for renal dialysis . In remote Australia, the incidence of Indigenous women needing dialysis is higher compared with Indigenous men . A retrospective cohort analysis, Australia and New Zealand Dialysis and Transplant (ANZDATA) Registry from 2001 to 2013 ( n = 21 832) reported that the incidence of dialysis in Indigenous women was higher than in Indigenous men (513 per million population and 406 per million population, respectively) .…”
Section: Discussionmentioning
confidence: 99%
“…The reverse was reported among non‐Indigenous people. Death associated with renal diseases between 1998 and 2012 was 3.9 times higher in Indigenous females and 2.6 times higher for Indigenous males when to compared with non‐Indigenous Australians . The causes of these disparities need to be fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…About 1.7 million Australians have CKD, and the total costs attributable to CKD in 2012 were estimated to be $4.1 billion, including $2.5 billion in direct health care costs . The greater burden of CKD among Australian Aboriginals and Torres Strait Islanders (Indigenous Australians) than among other Australians is well documented; the incidence of end‐stage kidney disease is 4.9 times as high among Indigenous men and 8.0 times as high among Indigenous women as among non‐Indigenous Australians, and the incidence of CKD increases with remoteness . Further, the mean age of Indigenous patients commencing renal replacement therapy (RRT) is lower .…”
mentioning
confidence: 99%